2017
DOI: 10.1037/adb0000258
|View full text |Cite
|
Sign up to set email alerts
|

An application of deviance regulation theory to reduce alcohol-related problems among college women during spring break.

Abstract: Spring break (SB) can lead to heavy episodic drinking and increased alcohol-related risks. This may be especially relevant for women. The current study utilized deviance regulation theory to increase the use of protective behavioral strategies (PBSs) among female college students on SB. Female college students going on SB (n = 62) completed a screening, a pre-SB intervention (where they were randomly assigned to receive either a positively or negatively framed message about individuals who do or do not use PBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 40 publications
5
40
0
Order By: Relevance
“…Thus, the current study sought to evaluate the association between PBS use, alcohol use, and alcohol-related problems as a function of perceived frequency of PBS use in the context of positive information about individuals that use PBS or negative information about individuals that do not. This approach is consistent with DRT, and has been shown to modify PBS use and subsequently substance use-related outcomes (Dvorak, Kramer, et al, 2018; Dvorak et al, 2017; Dvorak et al, 2015; Dvorak, Raeder, et al, 2018; Sargent et al, 2018). The results suggest that the intervention has DRT consistent effects on PBS use, though limited, if any, direct effects on alcohol use and related problems.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…Thus, the current study sought to evaluate the association between PBS use, alcohol use, and alcohol-related problems as a function of perceived frequency of PBS use in the context of positive information about individuals that use PBS or negative information about individuals that do not. This approach is consistent with DRT, and has been shown to modify PBS use and subsequently substance use-related outcomes (Dvorak, Kramer, et al, 2018; Dvorak et al, 2017; Dvorak et al, 2015; Dvorak, Raeder, et al, 2018; Sargent et al, 2018). The results suggest that the intervention has DRT consistent effects on PBS use, though limited, if any, direct effects on alcohol use and related problems.…”
Section: Discussionmentioning
confidence: 72%
“…This study examined the effects of a brief Deviance Regulation Theory (DRT) intervention on PBS use among college student drinkers. Previous research has shown that PBS use may mitigate alcohol consumption and alcohol-related problems (Barnett et al, 2007; Dvorak et al, 2017; Dvorak et al, 2016; Dvorak et al, 2015; Larimer et al, 2007; Martens et al, 2007; Martens et al, 2011; Pearson, 2013). However, interventions specifically targeting PBS have had mixed results (see LaBrie et al, 2015; Martens et al, 2013; Sugarman & Carey, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations